2016
DOI: 10.1149/07506.0011ecst
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Atmospheric-Pressure Spatial ALD of Al2O3 and ZrO2

Abstract: Non-thermal plasma sources are known to lower the operation temperatures and widen the process windows in thermal ALD of thin-film materials. In spatial ALD, novel plasma sources with exceptional dimensional and chemical stability are required to provide the flow geometries optimized for efficient transport and use of radicals (O, N, H, OH, NH, etc.).This paper describes our preliminary efforts to provide and examine the required linear scalable plasma sources in spatial ALD reactors. The effectiveness of clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In this configuration, one ALD cycle is achieved after completing a full rotation of the substrate table such that the substrate surface is sequentially exposed to each zone (i.e., precursor, inert gas, co-reactant, and inert gas). To generate the plasma, an atmospheric-pressure dielectric barrier discharge (DBD) plasma source with an alumina dielectric was used …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this configuration, one ALD cycle is achieved after completing a full rotation of the substrate table such that the substrate surface is sequentially exposed to each zone (i.e., precursor, inert gas, co-reactant, and inert gas). To generate the plasma, an atmospheric-pressure dielectric barrier discharge (DBD) plasma source with an alumina dielectric was used …”
Section: Methodsmentioning
confidence: 99%
“…To generate the plasma, an atmospheric-pressure dielectric barrier discharge (DBD) plasma source with an alumina dielectric was used. 52 SiO 2 films were deposited on Si wafers using bisdiethylaminosilane (BDEAS) as the silicon precursor and Ar−O 2 plasma as the co-reactant. The BDEAS precursor was contained in a bubbler kept at 20 °C.…”
Section: Experimental Section 31 Deposition Conditions and Materialsmentioning
confidence: 99%
“…[67] Secondly, and as has been shown above, in some cases the use of plasma activation can contribute to an increase in the deposition rate and film quality. While atmospheric plasma has already been implemented for the deposition of oxides and metals with SALD, [68,143,150,[169][170][171] scaling up to large substrates will remain a technical challenge. As for Batch ALD, plasma activation can only be done with remote plasma solutions, thus limiting the chemistry that can be performed in such HT ALD reactors.…”
Section: -Outlook/perspectivesmentioning
confidence: 99%
“…138 To benefit from the excellent isolation of the spatial regions that atmospheric pressure brings, spatial ALD using atmospheric-pressure plasma has been developed by both the Netherlands organization for applied scientific research (TNO) and the University of Wuppertal independently (first reported in 2015). [126][127][128][129][130]139 In both cases, surface dielectric barrier discharge (SDBD) plasmas are used as shown in Fig. 6.…”
Section: Spatial Aldmentioning
confidence: 99%